Is Atrial Fibrillation a Risk Factor for Gastroesophageal Reflux Disease Occurrence?. Issue 43 (October 2015) - Hwang, Jae Jin; Lee, Dong Ho; Yoon, Hyuk; Shin, Cheol Min; Park, Young Soo; Kim, Nayoung
Abstract : Abstract: Recent studies have reported an association between gastroesophageal reflux disease (GERD) and atrial fibrillation (AF). The objective of the present study was to evaluate whether AF is one of the risk factors for GERD occurrence. In this hospital-based, retrospective, case–control study, the patients were classified into 2 groups. The patients diagnosed with new AF were assigned to the AF group (n = 1612); those diagnosed without AF and GERD were assigned to the control group (n = 1612). The subjects in the control group were selected from outpatients of total healthcare center without a history of AF or GERD, and matched for age and gender. We evaluated the incidence of GERD and risk factors for GERD occurrence between the 2 groups. The number of patients experiencing occurrence of GERD during the follow-up period was significantly higher in the AF group than those in the control group, respectively (129 patients vs 98 subjects, P  = 0.037). The incidence of GERD was significantly higher in the AF group than in the control group by Kaplan–Meier analysis with log-rank test ( P  = 0.008). The AF group's adjusted hazard ratio of GERD occurrence against that of the control group was 1.37 (95% confidence interval [CI]: 1.16–1.57; P  = 0.009) according to Cox's proportional hazard model. The presence of AF appears to increase the incidence of GERD and may be considered a risk factor for the development of GERD. Further, large prospective and cohort studies will be required to better establish the correlation of GERD with AF.